Literatur Review : Dampak Implementasi Internal Control Over Financial Reporting, Whistleblowing System dan Internal Audit Terhadap Fraud Prevention - Kristianti, Indah (Universitas 17 Agustus 1945 Jakarta, 2025)
This study aims to examine and analyze the role of Internal Control Over Financial Reporting (ICoFR), Whistleblowing System, and Internal Audit in Fraud Prevention efforts in companies. The research approach used is a literature review, namely by examining various sources of scientific literature, research reports, and current regulations. The results of the study indicate that the effective implementation of internal control over financial reporting can improve the reliability of financial reporting and reduce the opportunity for fraud. Meanwhile, the whistleblowing system has been proven to play a significant role in detecting and preventing fraud by increasing transparency, accountability, and deterring potential perpetrators. On the other hand, independent and professional internal audit strengthens the internal control system and provides early warning of potential deviations.